Photodynamic Therapy Based on Graphene and MXene in Cancer Theranostics - Gazzi, Arianna; Fusco, Laura; Khan, Anooshay; Bedognetti, Davide; Zavan, Barbara; Vitale, Flavia; Yilmazer, Acelya; Delogu, Lucia Gemma (Frontiers in Bioengineering and Biotechnology, 2019)
Cancer is one of the leading causes of death in the world. Therefore, the development of new advanced and targeted strategies in cancer research for early diagnosis and treatment has become essential to improve diagnosis outcomes and reduce therapy side effects. Graphene and, more recently, MXene, are the main representatives of the family of two-dimensional (2D) materials, and are widely studied as multimodal nanoplatforms for cancer diagnostics and treatment, in particular leveraging their potentialities as photodynamic therapeutic agents. Indeed, due to their irreplaceable physicochemical properties, they are virtuous allies for photodynamic therapy (PDT) in combination with bioimaging, photothermal therapy, as well as drug and gene delivery. In this review, the rapidly progressing literature related to the use of these promising 2D materials for cancer theranostics is described in details, highlighting all their possible future advances in PDT.